(untitled) (Medico Legal Update, 2021)
Background: Malaria is still one of the public health problems that can cause death primarily in high-risk groups. High incidence of malaria caused by unhealthy environment and patterns of Society behavior. Objectives: Assessing the relationship between environmental factors and the society behavior factors with malaria incidence. Method: This is a case-control study. Samples were taken using sampling purposive with criteria: Age 7-50 years and case groups were noted as clinical malaria patients. Data is collected by observing and filling out questionnaires. Risk factors are analyzed using the Chi-Square test, knowing the risks with the odds ratio. The dominant risk factors were analyzed using binary logistic regression. Results: The variable associated with the malaria incident is ventilation (0,000), 2.5 (1.6-4.1), ceiling (0,015), 1.7 (1.1-2.7), puddles around the house (0,005), 1.9 (1.2-3.0), using of mosquito nets (0,000), 4.1 (2.4-6.4) and using mosquito repellent (0.001), 2,2 (1,4-3,5). Conclusion: The proven environmental factors associated with malaria incidents are ventilation, ceilings, and puddles around the house. The Society behavior factor associated with malaria incidents is using mosquito nets and using mosquito repellent. Proves that the use of mosquito nets is a major risk factor for malaria incidents, with a risk of 4.3 times greater in those who when sleeping at night do not use mosquito nets.